2019
DOI: 10.1007/s13197-018-03555-y
|View full text |Cite
|
Sign up to set email alerts
|

Elemental composition and nutritional value of Araucaria angustifolia seeds from subtropical Brazil

Abstract: Consumed by populations in South America, Araucaria angustifolia seeds have received little study regarding elemental composition and nutritional value. Thirty-five seed sites from subtropical Brazil were sampled and seed concentrations of C,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 17 publications
0
12
3
Order By: Relevance
“…To extend the chemical characterization of piñón tissues, including their nutritional valorization, their elemental composition was determined by EDXRF (Table 1). Piñón endosperm composition (97% w/w of edible pulp) was similar to that described for Brazilian piñones [52]. In this regard, one serving of piñones (14 pulps from fresh piñones) contains essential elements, such as P, K, Mn, Fe, Cu, and Zn, in significant nutritional concentrations, as well as Rb [53].…”
Section: Phytochemical Analysis Of Piñón Extractsmentioning
confidence: 72%
“…To extend the chemical characterization of piñón tissues, including their nutritional valorization, their elemental composition was determined by EDXRF (Table 1). Piñón endosperm composition (97% w/w of edible pulp) was similar to that described for Brazilian piñones [52]. In this regard, one serving of piñones (14 pulps from fresh piñones) contains essential elements, such as P, K, Mn, Fe, Cu, and Zn, in significant nutritional concentrations, as well as Rb [53].…”
Section: Phytochemical Analysis Of Piñón Extractsmentioning
confidence: 72%
“…P was accumulated in the order: needles > branches > stem. Barbosa et al (2019) found higher P concentrations (2.77 to 5.99 g kg -1 ) in A. angustifolia seeds, indicating probable remobilization of the nutrient, especially of the needles and part of the branches, which fall during the winter.…”
Section: Effect Of P Fertilizationmentioning
confidence: 83%
“…The RDA was used to predict the estimated demands of the inorganic components and proteins (IOM, 2006; WHO, 2012; WHO/FAO, 2004). Portions containing 100 g of pinhão almonds (wet basis) were used, considering that they are normally consumed with a moisture content of 45%, and, in order to obtain better consumption conditions, a 55 g portion (dry basis) was used (Barbosa et al., 2019).…”
Section: Methodsmentioning
confidence: 99%
“…In this way, the pinhão is a source of Cu (42.2%), P (31.1%), K (23.5%), and Zn (22.1%). The results of Barbosa et al (2019) indicate that raw almonds are a source of Cu (43.6%), P (32.8%), Mn (25.0%), and K (18.5%), whereas the results of Schveitzer et al (2014) indicate that the pinhão are a source of Fe (81.4%), Mn (52.4%), P (29.4%), and Cu (22.2%). This reveals several differences, which may be attributed to their origin and temporal variations.…”
Section: Nutritional Contribution Of the Pinhão Almonds To The Dietmentioning
confidence: 98%
See 1 more Smart Citation